Detecting Hidden Illegal Online Gambling on .go.id Domains Using Web Scraping Algorithms - Muchlis Nurseno; Umar Aditiawarman; Haris Al Qodri Maarif; Teddy Mantoro (Universitas Bumigora, 2024)
The profitable gambling business has encouraged operators to promote online gambling using black hat SEO by targeting official sites such as government sites. Operators have used various techniques to prevent search engines from distinguishing between genuine and illegal content. This research aims to determine whether websites with the go.id domain have been compromised with hidden URLs affiliated with online gambling sites. The method used in this research is an experiment using a FOFA.info dataset containing a complete list of 450,000 .go.id domains. A web scraping algorithm developed in Python was used to identify potentially compromised websites from the targeted listby analyzing gambling-related keywords in local languages, such as ’slot,’ ’judi,’ ’gacor,’ and ’togel'. The results showed that 958 of the 1,482 suspected.go.id sites had been compromised with an accuracy rate of 99.1%. This implies that security gaps have been exploited by illegal online gambling sites, posing a reputational risk to the government. Lastly, the scrapping algorithm tool developed in this research can detect illegal online gambling hidden in domains such as .ac.id, .or.id, .sch.id, and help authorities take necessary action.